Model Integrasi Islam Dan Sains Dan Implementasinya Terhadap Siswa/i SMA Trensains Tebuireng - Sarif, Abdullah (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2023)
Trensains Tebuireng High School is an educational institution that implements Prof. Agus Purwanto, D.Sc concept ideas in the development of the Islamization of contemporary science which places the verses of the Qur'an as a source of knowledge (epistemology of knowledge), with this dynamic the Trensains Tebuireng High School develops the Trensains High School curriculum which is directed at facilitating this idea at the implementation level, as well as being directed to realize the mandate of the law as stated in Law Number 20 of 2003. One manifestation of the realization of the integration of Islamic values ​​and science in Indonesia is that many schools at the secondary level integrate Islamic values ​​in their learning curriculum, even though in their implementation understanding of integration is not the same between institutions. Thus the researchers focused on examining the model and application of the integration of Islamic values ​​and science in Trensains Tebu Ireng Senior High School (SMA). The formulation of the problem is why the integration of Islamic values ​​and science is very important in modern times? How is the integration model of Islamic values ​​and science implemented in Trensains Tebu Ireng Senior High School? In this study, researchers used a descriptive qualitative research method with a type of field research conducted at Trensains PP High School. Tebuireng Jombang. The data collection techniques used are observation, interviews and documentation. Data analysis is in the form of data reduction, data presentation and drawing conclusions. From the discussion it can be concluded that the integration of Islamic values ​​and science is very important and a necessity in modern times. Integration is carried out to deal with the complexity of thought from secular-liberal Western hegemony in an effort to fortify students themselves from the context of Islamic scholarship and science. It is very important to design a curriculum that integrates Islam and science so that our students are not indoctrinated with the dichotomy of general science and religious knowledge.